Perampanel in the general population and in people with intellectual disability: Differing responses. (July 2017) - Shankar, Rohit; Henley, William; Wehner, Tim; Wiggans, Carys; McLean, Brendan; Pace, Adrian; Mohan, Monica; Sadler, Martin; Doran, Zoe; Hudson, Sharon; Allard, Jon; Sander, Josemir W.
Highlights: No large scale comparative study has yet been conducted for any AED in people with ID. The UK Ep-ID Register looks at outcomes of different AEDs beginning with PER. People with severe ID had better retention & efficacy than mild ID/general population. There is no evidence of any obvious concerns to prescribe PER in people with ID. Titration and past mental or behavioural issues can influence retention. Abstract: Purpose: There is a shortfall of suitably powered studies to provide evidence for safe prescribing of AEDs to people with Intellectual Disability (ID). We report clinically useful information on differences in response to Perampanel (PER) adjunctive treatment for refractory epilepsy between ID sub-groups and general population from the UK Ep-ID Research Register. Method: Pooled retrospective case notes data of consented people with epilepsy (PWE) prescribed PER from 6 UK centres was classified as per WHO guidance into groups of moderate -profound ID, mild ID and General population. Demographics, concomitant AEDs, starting and maximum dosage, exposure length, adverse effects, dropout rates, seizure type and frequency were collected. Group differences were reported as odds ratios estimated from univariable logistic regression models. Results: Of the 144 PWE (General population 71, Mild ID 48, Moderate to profound ID 48) examined the association between withdrawal and ID type was marginally statistically significant (p = 0.07). Moderate to profound ID PWE were less likely to come off PER compared to mild ID (OR = 0.19, CI = 0.04–0.92, p = 0.04). Differences in mental health side effects by groups was marginally statistically significant (p = 0.06). Over 50% seizure improvement was seen in 11% of General population, 24% mild ID and 26% Moderate to profound ID. Conclusions: PER seems safe in PWE with ID. It is better tolerated by PWE with Moderate to profound ID than PWE with higher functioning. Caution is advised when history of mental health problems is present. The standardised approach of the Ep-ID register UK used confirms that responses to AEDs by different ID groups vary between themselves and General population.